Teaching Tasks and Comprehensive Approach of Independent Study in General Practitioner's Training - Luis Alberto Mass Sosa; Pedro Miguel Milián Vázquez; Dianexis Susana Simón González; Ana Margarita López Rodríguez del Rey; Alberto Roteta Dorado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
It can be asserted that teaching tasks ensure a more comprehensive approach of independent study. This is possible when they respond to an extensive training guidance, to a comprehensive approach and when they are articulated from proposals related to the subjects generated by the teaching staff of the academic year, which is a methodological, strategic and projective context for making decisions. Teaching tasks should also be implemented through General Medicine, as a comprehensive discipline and element of cohesion with other disciplines, which allows linking the course with the social, economic, cultural and research reality of students. This article aims to reflect on the role of teaching tasks in achieving a more comprehensive approach of students´ independent study, a critical activity in the development of cognitive independence since the beginning of the general practitioner's training.